ANALISIS MOTIVASI MENGAJAR GURU ATAS IMPLEMENTASI KURIKULUM MERDEKA DI SMP BHINA DHARMA 2 KOTA BANDUNG - Nugraha, Ios Susila (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to measure the level of motivation of teacher due to the implementation of Kurikulum Merdeka at SMP Bhina Dharma 2 Bandung. This is considered important because majority teachers are still confuse and lack of understanding to implement Kurikulum Merdeka, leading a decreasing level of motivation to teach. Meanwhile, motivation is an essential factor to improve teacher"™s ability in order to plan, practice, and assess the curriculum used at schools to obtain the best learning outcomes. Therefore, it is important to measure how the level of teacher"™s motivation in teaching activity. This is a descriptive quantitative research with survey method, using questionnaire as the main instrument to reachout the purpose of the research. Further, this research used a total sampling technique, reaching 26 respondents. Then, the result revealed that teahers at SMP Bhina Dharma 2 Bandung have a good enough motivation to teach based on Kurikulum Merdeka implementation, reaching 67,31%. Further, this research also finds that there is a difference level of motivation among teachers which caused by the length of their experience as a teacher